Severe Acute Lung Injury After H2O2 Irrigation of an Aneurysmal Bone Cyst in an 8-Year-Old Girl: A Case Report. Issue 3 (15th March 2021) - Waldvogel, Salome; Zutter, Andreas; Krieg, Andreas H.; Trachsel, Daniel
Abstract : An 8-year-old girl developed severe acute lung injury after irrigation of a pelvic aneurysmal bone cyst with H2 O2 and filling with bone cement. Sudden profound oxygen desaturation occurred on the operating table when the patient was turned from the prone to the supine position. After a brief improvement in her oxygenation, the girl developed rapidly progressing severe respiratory failure necessitating reintubation and hour-long manual ventilation, while copious amounts of hemorrhagic frothy fluids were aspirated through the endotracheal tube. The patient started to improve after 24 hours and eventually made a full recovery. We hypothesize that the incident was caused by gas embolization and pulmonary endothelial damage by H2 O2 .